Sumoylation-deficient phosphoglycerate mutase 2 impairs myogenic differentiation - Zhang, Yi; Beketaev, Ilimbek; Ma, Yanlin; Wang, Jun (Frontiers in Cell and Developmental Biology, 2022)
Phosphoglycerate mutase 2 (PGAM2) is a critical glycolytic enzyme that is highly expressed in skeletal muscle. In humans, naturally occurring mutations in PGAM2 have been etiologically linked to glycogen storage disease X (GSDX). PGAM2 activity is regulated by several posttranslational modifications such as ubiquitination and acetylation. Here, we report that PGAM2 activity is regulated by sumoylation—a covalent conjugation involved in a wide spectrum of cellular events. We found that PGAM2 contains two primary SUMO acceptor sites, lysine (K)49 and K176, and that the mutation of either K to arginine (R) abolished PGAM2 sumoylation. Given that K176 is more highly evolutionarily conserved across paralogs and orthologs than K49 is, we used the CRISPR-mediated homologous recombination technique in myogenic C2C12 cells to generate homozygous K176R knock-in cells (PGAM2K176R/K176R). Compared with wild-type (WT) C2C12 cells, PGAM2K176R/K176R C2C12 cells exhibited impaired myogenic differentiation, as indicated by decreased differentiation and fusion indexes. Furthermore, the results of glycolytic and mitochondrial stress assays with the XF96 Extracellular Flux analyzer revealed a reduced proton efflux rate (PER), glycolytic PER (glycoPER), extracellular acidification rate (ECAR), and oxygen consumption rate (OCR) in PGAM2K176R/K176R C2C12 cells, both at baseline and in response to stress. Impaired mitochondrial function was also observed in PGAM2K176R/K176R P19 cells, a carcinoma cell line. These findings indicate that the PGAM2-K176R mutation impaired glycolysis and mitochondrial function. Gene ontology term analysis of RNA sequencing data further revealed that several downregulated genes in PGAM2K176R/K176R C2C12 cells were associated with muscle differentiation/development/contraction programs. Finally, PGAM2 with either of two naturally occurring missense mutations linked to GSDX, E89A (conversion of glutamic acid 89 to alanine) or R90W (conversion of arginine 90 to tryptophan), exhibited reduced PGAM2 sumoylation. Thus, sumoylation is an important mechanism that mediates PGAM2 activity and is potentially implicated in PGAM2 mutation-linked disease in humans.